Comparative Analysis of Single and Tapering FSH Doses on Follicular and Oocyte Yield in Sahiwal Cows - Golusu, Sai Charan; G, Aruna Kumari; K, Chandrasekhar Reddy; J, Radhakrishna Rao; K, Ramachandra Reddy; K, Venkata Ramana; K, Sravika (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study was conducted at Embryo Transfer & In vitro Fertilization (ET & IVF) laboratory, College of Veterinary Science, Korutla, Telangana. This study assessed the effects of single and multiple doses of follicle stimulating hormone (FSH) stimulation protocols on ovarian follicular development, oocyte retrieval, oocyte quality, in-vitro maturation (IVM) in Sahiwal cows. Thirty cows, irrespective of their estrous cycle stage, were categorized into three groups: Group 1 (single dose FSH, n = 10), Group 2 (tapered FSH doses, n = 10) and Group 3 (unstimulated controls, n = 10). Ovum pickup (OPU) was conducted following FSH stimulation in Groups 1 and 2, while Group 3 underwent OPU without hormonal stimulation. Retrieved oocytes were graded and subjected to IVM. Both FSH stimulation protocols significantly increased the follicular count (Group 1: 20.51 ± 2.30; Group 2: 22.11 ± 2.21; Group 3: 5.61 ± 0.65) and the number of recovered oocytes per cow (Group 1: 11.81 ± 1.80; Group 2: 15.81 ± 2.45; Group 3: 2.81 ± 0.29). FSH stimulated groups exhibited greater number of oocytes with cumulus cell expansion and first polar body extrusion than the control group, although the rates of Cumulus cell expansion and extrusion in percentages did not differ significantly. In conclusion, both single dose and tapering doses FSH stimulation protocols effectively promoted follicular development and improved oocyte recovery in Sahiwal cows.